2006
DOI: 10.1073/pnas.0602477103
|View full text |Cite
|
Sign up to set email alerts
|

p63heterozygous mutant mice are not prone to spontaneous or chemically induced tumors

Abstract: Homology between p63 and p53 has suggested that these proteins might function similarly. However, the majority of data from human tumors have not supported a similar role for p63 in tumor suppression. To investigate this issue, we studied spontaneous tumorigenesis in p63؉͞؊ mice in both WT and p53-compromised backgrounds. We found that p63؉͞؊ mice were not tumor prone and mice heterozygous for both p63 and p53 had fewer tumors than p53؉͞؊ mice. The rare tumors that developed in mice with compromised p63 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 41 publications
4
77
1
1
Order By: Relevance
“…Although p63 was originally anticipated to function as a tumor suppressor similarly to p53, there is also evidence that p63 functions as an oncogene (27,45). Recently, disparate reports have emerged regarding the tumor predisposition of mice heterozygous for p63 and p63/p53 (25,26,46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although p63 was originally anticipated to function as a tumor suppressor similarly to p53, there is also evidence that p63 functions as an oncogene (27,45). Recently, disparate reports have emerged regarding the tumor predisposition of mice heterozygous for p63 and p63/p53 (25,26,46).…”
Section: Discussionmentioning
confidence: 99%
“…While p63 has been reported to be absent or reduced in some human cancers, including basal cell carcinomas (18), it has more frequently been reported to be overexpressed in various tumors (19,20), including non-melanoma skin cancers (21)(22)(23)(24). Similarly, conflicting data from mice heterozygous for p63 have not resolved whether p63 is a tumor suppressor or oncogene (25)(26)(27).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…7,8 In contrast to TP53, which plays critical roles in regulating multiple cellular pathways and is mutated in many human cancers (reviewed in references 9-11), TP63 is rarely mutated, 12,13 and its role in cancer is not yet clarified. Data from mouse models are also inconclusive: although some studies show that p63 ϩ/Ϫ mice are not tumor prone, 14 other groups reported that p63 ϩ/Ϫ mice developed spontaneous tumors, including squamous cell carcinoma and sarcomas. 15 Despite the structural and partly functional identity among the TP53 family members, studies in knockout mice demonstrate significant functional differences among them.…”
mentioning
confidence: 99%
“…TP63 has two transcription initiation sites and is subject to extensive alternative splicing, giving rise to at least six isotypes having various and opposing activities (Figure 1). 12,14 One class of p63 isoforms contains the N-terminal transactivation domain (TA a, b, g), homologous to that of p53, whereas the other class of p63 isoforms lacks this domain (DN a, b, g) but is still transcriptionally active. 15 The balance between these two groups influences proper epidermal morphogenesis and the role of p63 in stem cell maintenance and differentiation seems to be the basis for most of the defects.…”
Section: Introductionmentioning
confidence: 99%